2022
DOI: 10.1111/jcmm.17622
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 plasma proteome reveals novel temporal and cell‐specific signatures for disease severity and high‐precision disease management

Abstract: The disease varies significantly from asymptomatic to severe illnessthe latter is associated with organ dysfunction and risk of death. The pathophysiology of severe disease is dominated by dysfunctional immunity, with either intensified immune or low immune responses. [4][5][6][7] The uncertainty in disease severity and progression makes uniform COVID-19 management difficult, indicating that patients could benefit from a precision medicine approach. 8-12 Among the next generation technologies used to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…Our COVID-19 ICU patients were similar to those reported in earlier cohorts [ 3 , [33] , [34] , [35] , [36] ] with respect to demographic, comorbidities and clinical presentation. In contrast to Wave-1 patients, Wave-3 COVID-19 patients had higher MODS and SOFA scores, and were more likely to have received invasive mechanical ventilation and steroid treatment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our COVID-19 ICU patients were similar to those reported in earlier cohorts [ 3 , [33] , [34] , [35] , [36] ] with respect to demographic, comorbidities and clinical presentation. In contrast to Wave-1 patients, Wave-3 COVID-19 patients had higher MODS and SOFA scores, and were more likely to have received invasive mechanical ventilation and steroid treatment.…”
Section: Discussionsupporting
confidence: 80%
“…Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2; patients are often admitted to the intensive care unit (ICU) for increased monitoring and potential life-saving interventions, where the mortality rate can be high [ 1 ]. COVID-19 induces an innate immune response [ 2 , 3 ] that includes increased interferons, tumor necrosis factor, bradykinin, serine proteases, soluble thrombomodulin and clot lysis times [ 4 8 ], thereby contributing to microvascular and thrombotic disease [ 9 , 10 ]. A humoral immune response follows the innate reaction in critically ill COVID-19 patients, with robust production of SARS-CoV-2-specific antibodies [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 binds to an angiotensin-converting enzyme 2 (ACE2) receptor expressed on the surfaces of many cells for entry (Yuki et al 2020 ). COVID-19 severity varies greatly with some experiencing mild symptoms to others experiencing multiorgan failure associated with extracellular matrix changes, impaired immune cell homing and programmed cell death (Iosef et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of accurate Long-COVID-specific biomarkers allows for early disease detection, accurate diagnosis, prognosis and/or targeted therapeutics. Advanced proteomic techniques, such as proximity extension assays [PEA; (Assarsson et al 2014 ; Lundberg et al 2011 ))] have great potential for an efficient and holistic approach to identifying disease and injury biomarkers (Fraser et al 2020a ; Fraser et al 2021 ; Iosef et al 2023 ; Van Nynatten et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the association between disease severity and the blood proteome in COVID-19 12,13,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . According to these studies, the most frequently observed and relevant disruptions observed in the proteome of critical illness include: neutrophil degranulation, cell cycle and transcriptional regulation and complement, coagulation, interferon, chemokine and interleukin signalling pathways (i.e., predominantly pathways involved in the acute phase response).…”
Section: Discussionmentioning
confidence: 99%